The role of mesenchymal stem cells in allergic rhinitis and its relationship with IL-10, plasma cells and regulatory T cells - Delfitri Munir; Iqbal Pahlevi Nasution; Lia Restimulia; Agung Putra; Nur Dina Amalina (Medicinski glasnik, 2023)
Aim: Allergic rhinitis (AR) is an IgE-mediated inflammation of the nose. Regulatory T cells (Tregs), plasma cells and inflammatory cytokines have shown to play a critical role in allergic airway inflammation. The aim of the study was to investigate the role of mesenchymal stem cells (MSCs) in generating Treg cells and plasma cells associated with regulating interlukin-10 (IL-10) in AR model. Methods: Fifteen male Wistar rats (6 to 8 weeks old) were randomly divided into three groups (control group, sham group, and MSCs treatment group). Ovalbumin (OVA) nasal challenge was conducted daily from day 15 to 21, and MSCs (1x106 ) were administrated intraperitoneally to OVA-sensitized rats on day 21. Sneezing was observed from day 24 to 27. The rats were sacrificed on day 24 and day 27. The expression of Treg and plasma cells was analysed by flow cytometry assay. The level of IL-10 was analysed under ELISA assay. Results: This study showed that the percentage of sneezing and rubbing times significantly decreased in MSCs treatment associated with the regulation of IL-10 level and plasma cell. This finding was aligned with the significant increase of Treg level. Conclusion: MSCs administration regulates IL-10 and plasma cell-mediated immune and inflammatory responses while increasing Treg cell production. MSCs may be a promising therapeutic target for treating Treg-mediated allergic diseases.
Keywords: allergic rhinitis; mesenchymal stem cells; regulatory T cells; IL-10